The use of machining features in set–up planning and fixture design to interface CAD to CAPP. (4th August 2014) - Ozturk, F.
This paper describes the use of features to interface CAD to CAPP. The introduction of computing technology and integration is a key factor towards the successful implementation of automated production process. The lack of automated communication between CAD and CAPP is the weak point of traditional CIM–based systems. FBD (feature–based design) is a key factor towards design and process planning integration from a process planning point of view. In this paper, proposed feature–based set–up planning and modular fixture design system is presented.